2006
DOI: 10.1007/s00441-006-0311-4
|View full text |Cite
|
Sign up to set email alerts
|

Nebulin isoforms of extraocular muscle

Abstract: The extraocular muscles (EOMs), which are responsible for reflexive and voluntary eye movements, have many unique biochemical, physiological, and ultrastructural features that set them apart from other skeletal muscles. For example, rodent EOMs lack M-lines and express EOM-specific myosin heavy chain (MYH13) and alpha-cardiac myosin heavy chain. Recent gene-expression profiling studies indicate the presence of other cardiac-specific proteins in adult EOMs. This interesting mixture of myofibrillar and cytoskele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…In our previous analysis of nebulin isoforms in the extraocular muscles, we failed to detect nebulette by western blot analysis [15]. In this study, we used a monoclonal antibody that recognizes four nebulin family members: nebulin, nebulette, LASP1 and (LASP2) and determined that LIM-nebulette, a splice variant of the nebulette locus, is indeed expressed in the extraocular muscles.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In our previous analysis of nebulin isoforms in the extraocular muscles, we failed to detect nebulette by western blot analysis [15]. In this study, we used a monoclonal antibody that recognizes four nebulin family members: nebulin, nebulette, LASP1 and (LASP2) and determined that LIM-nebulette, a splice variant of the nebulette locus, is indeed expressed in the extraocular muscles.…”
Section: Discussionmentioning
confidence: 88%
“…Immunolabeling was performed as described previously [15]. Briefly, cryostat sections were treated with 1% Triton X-100 in PBS for 15 min at 4°C, washed and then blocked in 1% normal goat serum in PBS for 1 hr at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, proteomic analysis of rodent EOMs confirmed the presence of α-cardiac actin [16]. We analyzed the nebulin isoforms present in EOMs and found that nebulin, not the cardiac-specific nebulette, is the major nebulin family member expressed [17]. The immunological detection of nebulin in EOMs does not, however, preclude the possibility that nebulette or its splice variant LIM-nebulette [18] is present in low abundance or within specialized domains in EOM fibers.…”
Section: Introductionmentioning
confidence: 99%